The Effect Of Digital Promotion Quality Dimensions On Consumer Purchase Intentions With Trust As A Mediating Variable (A Study At Smart Jaya Phone Store, Palu City) - Zihan Fhaiza Purnama Ramli; Ponirin Ponirin; Umar Syarifuddin; Farid Farid (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
The development of digital technology has transformed marketing strategies, making digital promotions an effective tool for reaching consumers. This study aims to analyze the influence of digital promotion quality dimensions on consumer purchase intentions with trust as a mediating variable at the Smart Jaya Phone Store in Palu City. This study uses a quantitative approach with a causal design. Data were collected through questionnaires from 116 customer respondents of the store and analyzed using SmartPLS-based Structural Equation Modeling (SEM). The results show that digital promotion quality has a positive and significant effect on purchase intentions, both directly and indirectly through trust. Trust is also proven to act as a partial mediator that strengthens the relationship between digital promotion quality and purchase intentions. The practical implications of this study emphasize the importance of digital promotion quality that is not only attractive but also able to build consumer trust to encourage sustainable purchase intentions.